Simulação computacional da propagação de cheia por diferentes rompimentos hipotéticos como subsídio para a gestão de segurança de barragens em Sergipe - Santa Rita, Leonardo de Carvalho Souza (2021)
Dams have been the solution used to ensure water security and development for civilizations. Despite the benefits, there are environmental impacts and risks of accidents associated with their use. The National Dam Safety Policy (PNSB) establishes guidelines and requirements to be followed by entrepreneurs and regulators, and, for dams with potential damage asociated classified as high, it requires the preparation of an Emergency Action Plan (EAP). To do so, hypothetical dam break scenarios must be simulated in order to obtain the flood’s spatial coverage in the downstream valley. In this regard, this work aimed to evaluate the hydrodynamic effects in the downstream valleys due to hypothetical ruptures of the Jacarecica I and Jacarecica II dams, in the state of Sergipe. Considering scenarios of most probable rupture (usual conditions) and extreme rupture (unusual conditions), flood inundation maps were elaborated and hydrostatic and hydrodynamic risk zoning was carried out. In addition to comparing the results obtained using the HEC-RAS hydrodynamic model with those provided by the National Water and Basic Sanitation Agency’s Simplified Methodology (MS), a sensitivity analysis of the HEC-RAS outputs was performed with varying input data. Results showed that the dam break scenarios cause floods that affect residential and agricultural areas, roads and highways, bridges and an industry before reaching the city of Riachuelo, about 18 km downstream of Jacarecica II, with minimum wave arrival times of 6 to 8 hours, and maximum depths and velocities close to 10 m and 5 m.s-1, respectively. It was also observed that the dams resist extreme hydrometeorological events without overtopping, even though these events cause significant natural flood. The inundation map simulated with HEC-RAS showed a similar format to the one developed by MS, although the spatial coverage was wider with MS. The sensitivity analysis showed that the triggers elevations and the inflows to the reservoirs are the input data that cause less convergence in the simulated flows, velocities and maximum depths. With rural and urban areas located inside the flood inundation mpas and subjected to significant wave depths and velocities, it is essential (and mandatory, according to the PNSB) that the dams’ EAPs are prepared as soon as possible.